KARAKTERISTIK ES KRIM HASIL MODIFIKASI DENGAN FORMULASI BUBUR TIMUN SURI (Cucumis melo L.) DAN SARI KEDELAI [Characteristics of Modified Ice Cream Formulated with Cucumis melo L. Puree and Soybean Milk] - . Oksilia; Merynda Indriyani Syafutri; Eka Lidiasari (Jurnal Teknologi dan Industri Pangan, 2012)
The objective of this research was to observe the physical and chemical characteristics of ice cream made with various formulations of Cucumis melo L. puree and soybean milk. The experiment was designed using Factorial Randomized Block Design with two treatments and each combination was replicated three times. The factors investigated were formulations of Cucumis melo L. puree (10, 12.5 and 15 %) and soybean milk (40, 50 and 60%). The ice cream’s viscosity, overrun and melting time were determined, where as protein, fat and potassium content were analyzed. The results showed that the interaction of Cucumis melo L. puree and soybean milk formulation had significant effect on viscosity and overrun. Modified ice cream made with 12.5% Cucumis melo L. puree and 40% soybean milk was the best formula for producing modified ice cream. The resulted ice cream had viscosity of 1.03 cP, overrun 53.93% and melting time 23,58 minutes, while the protein, fat and potassium content were 5.18%, 70% and 1083.33 mg/L, respectively.